2016
DOI: 10.24297/jaa.v5i2.5085
|View full text |Cite
|
Sign up to set email alerts
|

THE CHEMICAL COMPOSITION AND NUTRITIVE VALUE OF Brachiaria GRASS CULTIVARS AT KATUMANI DRYLAND RESEARCH STATION IN SOUTH EASTERN KENYA

Abstract: The study was conducted at Kenya Agricultural and Livestock Research Organisation, Katumani, Machakos to evaluate the herbage quality of Brachiaria grass cultivars in semi arid regions of Eastern Kenya. Brachiaria cultivars namely B. decumbens cv. Basilisk, Brachiaria hybrid  Mulato II, four Brachiaria brizantha cultivars Marandu, Xaraes, Piata, MG4 and Brachiaria humidicola cv Llanero were assessed with reference to their chemical and nutritive composition at 22, 24 and 28 weeks post seedling emergence. Rhode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
0
11
0
2
Order By: Relevance
“…In semi‐arid areas of Kenya (rainfall around 750 mm), Nguku, Musimba, et al. (2016) reported herbage accumulation of 4 Mg DM ha −1 for Mulato II, 16 wk after planting. Other results obtained in Colombia under rainfed conditions reported herbage accumulation of Mulato II ranging from 3.3 to 3.1 Mg DM ha −1 in rainy and dry season, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In semi‐arid areas of Kenya (rainfall around 750 mm), Nguku, Musimba, et al. (2016) reported herbage accumulation of 4 Mg DM ha −1 for Mulato II, 16 wk after planting. Other results obtained in Colombia under rainfed conditions reported herbage accumulation of Mulato II ranging from 3.3 to 3.1 Mg DM ha −1 in rainy and dry season, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It was tested in conservation agriculture systems in Madagascar; in integrated intercropping systems for controlling pests, weeds, and soil by the International Centre of Insect Physiology and Ecology in Kenya, Tanzania, and Ethiopia; and for intercropping forages in dairy systems in Uganda and Madagascar (Maass et al., 2015). On‐station investigation in semi‐arid Kenya showed that Mulato II had greater herbage accumulation (HA) and nutritive value (NV) under certain conditions, as compared to other tested African perennial native grasses (Machogu, 2013; Nguku, Musimba, et al., 2016; Nguku, Njari, et al, 2016). Although pest and disease issues associated with Mulato II have been reported in some areas, this hybrid continues to raise interest among African farmers and may play a role in improving agricultural systems in Africa (Maass et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Values reported in other evaluations with grasses are similar to the present study, e.g., 7 % in U. brizantha (Santiago et al, 2016), 8.5 % in U. decumbens, 9.5 % in Chloris gayana, and 10.6 % in U. brizantha cv. Xaraés (Nguku et al, 2016). Inorganic material in pastures is variable in ash concentration among species; normally up to 12% or more can be found in herbaceous plants and agricultural residues in early stages of growth.…”
Section: Ashmentioning
confidence: 99%
“…All these characteristics would contribute to increased photosynthetic activity and hence higher DM production. The yield increment might be due to the additional tillers developed, which brought an increase in leaf formation, leaf elongation, and stem development [31,32] . The current analysis result was agreeing with the finding of [33][34][35] who reported the highest total DMT observed at the last harvesting stage on wild Brachiaria grasses in different countries.…”
Section: Total Dry Matter Yield (Tdmy)mentioning
confidence: 99%